A micromechanical model of the evolution of stress and strain fields in ultrafine-grained metal structures under tension. (February 2013) - Collini, Luca; Bonardi, Alessandra
In this study, the authors present a micromechanical finite element modelling approach to the analysis of a set of ultrafine-grained polycrystalline copper structures. The models take into account both realistic grain distribution and the number of refinement passes of the microstructure. The grain size effect is successfully predicted, with non-uniform deformation and shear localization reproduced during global plastic flow in agreement with experimental observations. The models provide a useful tool with which to interpret damage and fracture mechanisms occurring in ultrafine-grained structures.